SEMIVARIOGRAM MODEL AND ESTIMATION OF ORDINARY KRIGING (Cases : THE NATIONAL EXAMINATION VALUE OF JUNIOR HIGH SCHOOL AT BANDUNG AND CIMAHI CITY) - KURNIA NOVITA SARI (NIM 20107044), RR.
The spatial process is a process which generalized by collection random variables which have index parameters as locations at a region. For measuring the linear dependent between observations which seperated by lag h, we can use semivariogram. Semivariogram is counted by experimental semivariogram which fitting with semivariogram models. Some semivariogram models that seldom used to representate the spatial correlation are exponential, spherical, and gauss model. That model are used in kriging method for interpolation the variable unobservation regionalized. In thesis, writer uses the National Examination value data of Junior High School at Bandung and Cimahi City. The National Examination include Indonesian Language, English Language, and Mathematics. Therefore, that discuss a method to get experimental semivariogram, choose semivariogram model, and analyze contour of estimation with Ordinary Kriging method.